Productive planning in an unstable country: The case of Argentina (2019-2023) - Daniel Schteingart (economic sociology. perspectives and conversations, 2024)
During the period 2019-2023, Argentina was governed by a coalition of different factions of Peronism, a party that traditionally made state-led industrialization part of its narrative. In this context, there was a prioritization of the productive development and industrial policy agenda, which increased its resources compared to the previous government (2015-2019), whose orientation had been more economically liberal.
Keywords: 300